Réponses

2012-09-23T18:51:07+02:00

A= 11+2(x-6)

= 11+2*x+2*(-6)

= 11+2x-12

= 2x-1

 

B= -3(2y-4)-2y

= -3*2y-3*(-4)-2y

= -6y+12-2y

= -4y+12

 

C= 7-4(8-2a)+a

= 7-4*8-4*(-2a)+a

= 7-32+8a+a

9a-25

 

D= (7-3x)(9x-3)

= 7*9x+7*(-3)-3x*9x-3x*(-3)

= 63x-21-27x²+9x

= 27x²+36x-21

 

E= (-2-3y)(4-8y)

= -2*4-2*(-3y)-3y*4-3y*(-8y)

= -8+6y-12y+24y²

= 24y²-6y-8

2012-09-23T18:54:02+02:00

A = 11 + 2 ( x - 6)

= 11 + 2X - 12

= 2x -1

 

B= -3 (2y - 4) - 2y

= -6y + 12 - 2y

= -8 y + 12

 

C = -7 -4 (8 - 2a) + a

= -7 -32 + 8a + a

= -39 + 9a

 

D = (7 - 3x) ( 9x - 3)

= 63x -21 - 27x² + 9x

= -27x² + 72x - 21

 

E = (-2 - 3y) (4 - 8y)

= -8 +16y -12y +24y²

= 24y² +4y - 8